Mandate Contracts - Díaz, Odavia Bueno; Loos, Marco B. M. (Principles of European Law, 2012)
In the context of the harmonisation of European contract law this is a hot topic: The new volume of the Principles of European Law deals with mandate contracts, i.e. contracts whereby an agent concludes a contract with a third party for the benefit of a principal. The Principles of European Law on Mandate Contracts do not only mirror the provisions on these contracts in the Draft Common Frame of Reference (DCFR), but also contain a more comprehensive explanation of these provisions. Moreover, they provide details on the functioning of mandate contracts in the laws of the Member States. Thus, the principles are conducive to advance the process of Europeanisation of private law.